Evaluasi Penerapan Sistem Pengendalian Internal dalam Bidang Akuntansi di PT Pupuk Indonesia Logistik - Naila Fattika Zahra; Mutya Paramita Pratita (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to evaluate the implementation of the Internal Control System (ISC) in accounting at PT Pupuk Indonesia Logistik, specifically related to fixed asset management and asset impairment testing based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. The study employed a qualitative descriptive method with a case study approach. Data were obtained through in-depth interviews, observations, and documentation involving relevant parties within the company. Data analysis was conducted through an interactive process of organizing, categorizing, presenting, and drawing conclusions.The results indicate that PT Pupuk Indonesia Logistik has formally implemented an Internal Control System based on the COSO framework, but its implementation has not been optimal. Key weaknesses were identified in the risk assessment process and control activities, particularly related to the assessment of fixed asset impairment. The company lacked detailed operational procedures, had not yet incorporated impairment risks into the risk register, and lacked an early warning system to detect asset impairment early. Furthermore, coordination between work units, data quality, and human resource competency did not fully support the effectiveness of internal controls. This situation led to a significant difference between the unaudited and audited financial statements for 2024 due to the correction of fixed asset impairment. This study concludes that the implementation of Internal Control Systems (SPI) at PT Pupuk Indonesia Logistik has not been fully effective in supporting the reliability of the company's financial reports. Therefore, the company needs to strengthen internal controls by developing more detailed impairment procedures, strengthening risk management, enhancing human resource competency, and optimizing the implementation of Internal Control over Financial Reporting (ICOFR)..